Implementasi Konsep Partisipasi Bermakna dalam Proses Pembentukan Undang-Undang: Studi Kasus Pembuatan Undang-Undang Nomor 17 Tentang Kesehatan Tahun 2023 - Mahatta, Afdhal; Febriyanto, Satrio Alif (Jurnal Ilmiah Penegakan Hukum, 2024)
The establishment of Law Number 17 Year 2023 on health has received enormous public attention. The magnitude of public awareness is not only due to significant changes in substance. More than that, reactions from the public, especially health professional organizations as the element of society most affected by the law, have caused a heated discourse in the community. The reaction arose because health professional organizations felt that they did not get significant participation in forming the health law. The issue of participation will be studied using the normative juridical method to find out regulations and theories related to ideal meaningful participation in creating a law. Furthermore, the normative juridical approach will be strengthened by using statistical data on aspirations and minutes from each public participation activity to examine public participation in forming Law Number 17 of 2023 on health. Based on the study's results, the formation of this law has fulfilled the elements of public participation quantitatively, with a note that only a few aspirations of civil society elements were accommodated